Investigation of mixing in binary surfactant solutions by surface tension and neutron reflection: Strongly interacting anionic/zwitterionic mixtures - Hines, J; Thomas, R; Garrett, P; Rennie, G; Penfold, J (1998)
Aqueous solutions of the strongly interacting anionic/zwitterionic surfactant mixture of sodium dodecyl sulfate (SDS) and dodecyl dimethylamino acetate (C12betaine) have been studied by means of surface tension and neutron reflection. The mixed critical micelle concentrations (cmc) were used to derive the interaction parameter βM for micellization, which was found to be large and negative. It was also found to be composition dependent and therefore not to obey the first-order approximation for the activity coefficients in the pseudo-phase separation approximation. The temperature dependence of the mixed cmc gave the thermodynamic excess functions for micellization; SE was found to be positive over most of the composition range. Application of the pseudo-phase separation model to surface tension data was used to show that the interaction parameter βσ in the surface layer is similarly large and negative. However, direct measurement of the surface concentrations using neutron reflection disagree with the predictions of the pseudo-phase separation model and indicate that βσ although negative, is much smaller in magnitude. The structure of the mixed layer was determined at three compositions and found to be significantly dehydrated in comparison with layers of the single surfactants, which may explain the positive excess entropies observed for both micellization and surface mixing. It is also suggested that changes of hydration on mixing invalidate the use of the pseudo-phase separation model and may be responsible for the deviations from the first-order model observed for both micellization and surface interaction.